2003
DOI: 10.1007/s00534-002-0760-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cell membrane damage during cold preservation sensitizes liver grafts to rewarming injury

Abstract: Our data show a constant glycerol release during cold storage, indicating a continuous injury to the cell membranes over time. Improvement in cell membrane protection during cold preservation could lead to improvement in liver transplantation outcome and acceptance of an extended period of cold ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 40 publications
3
34
1
Order By: Relevance
“…Organs from NHBD (non-heart-beating donors) seem to be an option to alleviate the problem of liver donor shortage effectively [1] . However, warm ischemia to the liver related to cardiac arrest remained a main obstacle to the use of livers from NHBD [2][3][4] . Moreover, in liver transplantation, the allograft sustains inevitable cold ischemia in addition to rewarming injury during liver reperfusion [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Organs from NHBD (non-heart-beating donors) seem to be an option to alleviate the problem of liver donor shortage effectively [1] . However, warm ischemia to the liver related to cardiac arrest remained a main obstacle to the use of livers from NHBD [2][3][4] . Moreover, in liver transplantation, the allograft sustains inevitable cold ischemia in addition to rewarming injury during liver reperfusion [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring may be extended into the post-transplantation period. During cold preservation of pig livers for up to 15 hours, there was a progressive increase of tissue glycerol concentrations (Nowak 2003). Pig livers stored cold for 24 hours after preservation with different solutions demonstrated increasing tissue glycerol concentrations that may correlate to liver enzyme release and other signs of tissue injury (Puhl 2006).…”
Section: Heart Preservationmentioning
confidence: 99%
“…It is not known whether the earlier described pathways for glycerol release during myocardial ischemia also apply to prolonged cold cardioplegic storage. Studies of porcine cold hepatic preservation have demonstrated glycerol accumulation with correlation to duration of storage (Nowak 2003), and demonstrated an association between higher glycerol concentrations and other signs of tissue injury (Puhl 2006). …”
Section: Myocardial Glycerolmentioning
confidence: 99%
“…Microdialysis can been used to monitor energy metabolism in severe brain injury [87] and in liver transplantation [88]. Raised lactate-to-pyruvate ratio (L/P ratio) and glycerol levels are reliable markers for ischaemia and cell membrane damage respectively [89].…”
Section: Monitoring Regional Perfusionmentioning
confidence: 99%